Women middle and senior managers - Bassirou Gueye (Economic and Social Reports)
Workforce diversity, particularly the inclusion of women in leadership roles, significantly enhances business performance by improving financial outcomes such as return on assets, equity and sales. Studies show that having a greater number of women in top management positions not only drives profitability but also contributes to a more innovative and resilient corporate culture.